Perancangan Mesin Cetak Biopellet Sekam Padi Dengan Menggunakan Software Solidwork 2016 - Billy Nugraha; Iwan Nugraha Gusniar; Dicky Gumelar (P3M Politeknik Negeri Cilacap, 2022)
Indonesia's consumption of energy increases significantly each year. While the reserves of energy are declining every year, alternative energy is needed. The waste treatment of rice husk biomass has been used for alternative energy, so the research aims to optimize the waste into fuel. The research site was conducted in Kelapa Dua Village, Jaya Subdistrict, Karawang Regency. To get the results of the design, there needs to be technological engineering to design production machines with the help of solidworks 2016 software. The research resulted in the form of compounding tools, as follow: Screw press diameter (Ds = 200 mm), screw height (hs = 65 mm), screw shaft diameter (dps = 70 mm), screw lift length (L = 420 mm), nominal screw diameter (Dn = 177.8 mm), screw lift width (Fd Max = 14 mm), screw spacing (pitch) (P = 60 mm), screw number (n = 7 threads), helix angle (β = 8), screw press power requirement (Pe = 119.27 watts), torque (T = 326.1 N.m), screw lift load (Ws = 141.5 N) and pressure developed on screw thread (PS = 1.65 N/mm2).